Analysis of regional CO2contributions at the high Alpine observatory Jungfraujoch by means of atmospheric transport simulations and δ13C - Pieber, Simone M.; Tuzson, Béla; Henne, Stephan; Karstens, Ute; Gerbig, Christoph; Koch, Frank Thomas; Brunner, Dominik; Steinbacher, Martin; Emmenegger, Lukas (Atmospheric chemistry and physics, 2022)
In this study, we investigated the regional contributions of carbon dioxide (CO2) at the location of the high Alpine observatory Jungfraujoch (JFJ, Switzerland, 3580ĝ€¯mĝ€¯a.s.l.). To this purpose, we combined receptor-oriented atmospheric transport simulations for CO2 concentration in the period 2009-2017 with stable carbon isotope (δ13C-CO2) information. We applied two Lagrangian particle dispersion models driven by output from two different numerical weather prediction systems (FLEXPART-COSMO and STILT-ECMWF) in order to simulate CO2 concentration at JFJ based on regional CO2 fluxes, to estimate atmospheric δ13C-CO2, and to obtain model-based estimates of the mixed source signatures (δ13Cm). Anthropogenic fluxes were taken from a fuel-type-specific version of the EDGAR v4.3 inventory, while ecosystem fluxes were based on the Vegetation Photosynthesis and Respiration Model (VPRM). The simulations of CO2, δ13C-CO2, and δ13Cm were then compared to observations performed by quantum cascade laser absorption spectroscopy. The models captured around 40ĝ€¯% of the regional CO2 variability above or below the large-scale background and up to 35ĝ€¯% of the regional variability in δ13C-CO2. This is according to expectations considering the complex Alpine topography, the low intensity of regional signals at JFJ, and the challenging measurements. Best agreement between simulations and observations in terms of short-term variability and intensity of the signals for CO2 and δ13C-CO2 was found between late autumn and early spring. The agreement was inferior in the early autumn periods and during summer. This may be associated with the atmospheric transport representation in the models. In addition, the net ecosystem exchange fluxes are a possible source of error, either through inaccuracies in their representation in VPRM for the (Alpine) vegetation or through a day (uptake) vs. night (respiration) transport discrimination to JFJ. Furthermore, the simulations suggest that JFJ is subject to relatively small regional anthropogenic contributions due to its remote location (elevated and far from major anthropogenic sources) and the limited planetary boundary layer influence during winter. Instead, the station is primarily exposed to summertime ecosystem CO2 contributions, which are dominated by rather nearby sources (within 100ĝ€¯km). Even during winter, simulated gross ecosystem respiration accounted for approximately 50ĝ€¯% of all contributions to the CO2 concentrations above the large-scale background. The model-based monthly mean δ13Cm ranged from -ĝ€¯22ĝ€¯‰ in winter to -ĝ€¯28ĝ€¯‰ in summer and reached the most depleted values of -ĝ€¯35ĝ€¯‰ at higher fractions of natural gas combustion, as well as the most enriched values of -ĝ€¯17ĝ€¯‰ to -ĝ€¯12ĝ€¯‰ when impacted by cement production emissions. Observation-based δ13Cm values were derived independently from the simulations by a moving Keeling-plot approach. While model-based estimates spread in a narrow range, observation-based δ13Cm values exhibited a larger scatter and were limited to a smaller number of data points due to the stringent analysis prerequisites.